Comparing the Diagnostic Accuracy of PSP Digital Intraoral Receptor Software Options in Assessment of Vertical Fractures of Mandibular Posterior Teeth: The Effects of Digital Image Processing Options on Detection of Vertical Root Fracture - Ranji, Paniz; Hafezi, Ladan; Lotfi, Fatemeh (Journal of Dental School, 2023)
Objectives Root fracture detection may be a challenging process due to difficulties in clinical and radiographic assessments. This study compared the diagnostic efficacy of Photostimulable Phosphor (PSP) intraoral digital receptor software alternatives for detection of vertical fractures in mandibular posterior teeth. Methods In this diagnostic research, 60 human mandibular posterior teeth were chosen. Vertical fracture was induced on half of teeth using a hammer through a random method. Thereafter, the broken pieces were glued together using a superglue, and placed inside a sheep mandible. Next, utilizing a digital intraoral technique and a PSP sensor, radiographic images of every tooth were taken. All radiographies were then subjected to computer adjustments such as sharpening, reverse-contrast, and enhancement. Three radiologists investigated the images of teeth after application of computer adjustments regarding existence of fracture. SPSS 22 was used for data analysis. Results Among processed images, sharpness had the highest accuracy (89.3%) followed by enhancement (89%), and reverse-contrast (87%). Statistically, no significant difference was observed in diagnosis of vertical fractures of mandibular posterior teeth regarding sensitivity, specificity, accuracy, as well as positive and negative predictive value among main images (no effect) and the images on which sharpness, reverse-contrast, and enhancement by software were applied (P-value>0.05). For intra-observer agreement, Kappa value > 0.70 and for inter-observer agreement, kappa value=0.50-0.7 were found. Conclusion Usage of sharpness, reverse-contrast, and enhancement software had no significant impact in diagnosing vertical root fracture of multi-rooted teeth (P-value>0.05).